2018
DOI: 10.1002/hyp.11518
|View full text |Cite
|
Sign up to set email alerts
|

Streambed restoration to remove fine sediment alters reach‐scale transient storage in a low‐gradient fifth‐order river, Indiana, USA

Abstract: Hyporheic restoration is of increasing interest given the role of hyporheic zones in supporting ecosystem services and functions. Given the prevalence of sediment pollution to waterways, an emerging restoration technique involves the removal of sediment from the interstices of gravel‐bed streams. Here, we document streambed sediment removal following a large, accidental release of fine sediment into a gravel‐bed river. We use this as a natural experiment to assess the impact of fine sediment removal on reach‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 89 publications
4
39
1
Order By: Relevance
“…The efficiency of river restoration structures can likely be improved by attending to design variables that can alter HZ functioning. Example variables include controlling hydraulic gradients (e.g., the height of a step [218]), manipulating hydraulic conductivities (e.g., with sediment coarsening [248]), changing flowpath geometries (e.g., with baffle walls [54,249] or hyporheic caps and increased HZ depth [33]), or shielding a structure from groundwater upwelling or downwelling (e.g., with a liner). Future research should focus on tailoring river restoration practices to deliver specific regulating ecosystem services, while also recognizing that in-channel structures alone are not able to overcome catchment-scale degradation of these services [250].…”
Section: Knowledge Exchange Between the Scientific Community And Restmentioning
confidence: 99%
“…The efficiency of river restoration structures can likely be improved by attending to design variables that can alter HZ functioning. Example variables include controlling hydraulic gradients (e.g., the height of a step [218]), manipulating hydraulic conductivities (e.g., with sediment coarsening [248]), changing flowpath geometries (e.g., with baffle walls [54,249] or hyporheic caps and increased HZ depth [33]), or shielding a structure from groundwater upwelling or downwelling (e.g., with a liner). Future research should focus on tailoring river restoration practices to deliver specific regulating ecosystem services, while also recognizing that in-channel structures alone are not able to overcome catchment-scale degradation of these services [250].…”
Section: Knowledge Exchange Between the Scientific Community And Restmentioning
confidence: 99%
“…Finally, we calculated the holdback of the system (H), which describes transport in a continuum ranging from piston flow (H = 0) to no movement of the solute (H = 1) [Danckwerts, 1953]. Ward et al [2018b] interpret higher values of H to indicate greater influence of transient storage on reach-scale transport. Holdback is calculated as:…”
Section: Short-term Storage Analysismentioning
confidence: 99%
“…While a trend was present, we also note that travel time based on tpeak exhibits less variation than discharge (coefficient of variation 1.00 for travel time compared to 1.49 for discharge). For context, a recent study by Ward et al [2018b] attempted to control for experiments with 20-min of advective time and accepted a range from 17 to 50 minutes as comparable. Thus, while our selection of study reach lengths was imperfect to achieve identical advective timescales, we contend that we have controlled for advective time in a more rigorous way than has been done in most previous studies.…”
Section: Basin-scale Trends From Synoptic Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fawn River restoration provided an opportunity to examine the effects of restoration on stream metabolism and nutrient spiraling in a real-world setting in which a limited number of physical and chemical variables-streambed sediment content and macrophyte abundance-were manipulated in a semi-controlled manner. In a companion study, Ward et al (2018) found that fine sediment removal likely increased surface water exchange with the hyporheic zone in Fawn River during high-flow periods. Increased surface-subsurface connectivity is expected to promote ecological functioning, including nutrient retention (Mendoza-Lera and Datry 2017).…”
Section: Introduction Backgroundmentioning
confidence: 95%